Breaking Barriers to Better Care: A Narrative Review on the Adoption of Single-Fraction Palliative Radiotherapy for Bone Metastases in Low- and Middle-Income Countries - Erika Galietta; Costanza M. Donati; Maria Vadala’; Francesco Cellini; Von Kaganda Bomboka; Romina Rossi; Milly Buwenge; Tigeneh Wondemagegnehu; Biniyam Tefera Deressa; A.F.M. Kamal Uddin; Mostafa A. Sumon; Marco Maltoni; et al. (Palliative Medicine Reports)
Introduction: Palliative radiotherapy is essential for managing bone metastases, providing effective pain relief, and improving quality of life. While multiple fractions of radiotherapy are commonly used in high-income countries, randomized studies have established single-fraction palliative radiotherapy as an equally effective standard for uncomplicated painful bone metastases. Despite its proven effectiveness, there is still some reluctance to adopt single-fraction palliative radiotherapy in high-income countries. In low- and middle-income countries, single-fraction palliative radiotherapy can address many challenges, such as limited resources and difficulties in delivering cancer care, by reducing the number of treatment sessions and improving patient accessibility. However, barriers to single-fraction palliative radiotherapy adoption in low- and middle-income countries remain. Materials and Methods: This narrative review examines the barriers to single-fraction palliative radiotherapy adoption for bone metastases in low- and middle-income countries and explores possible solutions. Results: It highlights the effectiveness and benefits of single-fraction palliative radiotherapy in resource-limited settings and emphasizes the need for a tailored approach that includes policy development, clinical guidelines, training, research, and community engagement. Conclusions: Ultimately, this collaborative effort can improve palliative care and patient outcomes, regardless of location or economic conditions.